2016
DOI: 10.1186/s12974-016-0526-6
|View full text |Cite
|
Sign up to set email alerts
|

Vascular-directed responses of microglia produced by methamphetamine exposure: indirect evidence that microglia are involved in vascular repair?

Abstract: BackgroundBrain microglial activations and damage responses are most commonly associated with neurodegeneration or systemic innate immune system activation. Here, we used histological methods to focus on microglial responses that are directed towards brain vasculature, previously undescribed, after a neurotoxic exposure to methamphetamine.MethodsMale rats were given doses of methamphetamine that produce pronounced hyperthermia, hypertension, and toxicity. Identification of microglia and microglia-like cells (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In a recent study, we found that METH results in pronounced microglia activation directed at vasculature, even in areas of the anterior medial dorsal hippocampus and lateral septum where there was no evidence of neurodegeneration or nerve terminal damage (Bowyer et al . ). We take these findings as further evidence of high glucose levels correlating with increased vascular damage.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In a recent study, we found that METH results in pronounced microglia activation directed at vasculature, even in areas of the anterior medial dorsal hippocampus and lateral septum where there was no evidence of neurodegeneration or nerve terminal damage (Bowyer et al . ). We take these findings as further evidence of high glucose levels correlating with increased vascular damage.…”
Section: Discussionmentioning
confidence: 97%
“…Neurotoxic exposures to either AMPH or METH that result in severe hyperthermia produce the most damage and disruption of vasculature in the thalamus along the border between the ventral intralaminar, ventromedial and ventromedial thalamic nuclei (Bowyer et al . , ). In this region, FJc labeling of degenerating neurons is only apparent at 48 h or more after AMPH or METH exposure, while the FJc+ neurons in the parietal cortex appear within 24 h. Thus, there is indirect evidence in the thalamus that vascular damage precedes neuronal death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CD68, a lysosomal activity marker expressed during inflammatory processes by microglia/macrophages, is regarded as a marker of M1 microglia/macrophages [ 13 , 17 , 18 ]. Activated microglia were reported to be labeled by CD11b immunoreactivity [ 19 ], and antibodies specific to CD206 and Ym1 are used to identify M2 microglia/macrophages [ 20 ]. In this study, it was observed that the ameboid Iba-1 positive microglia in the hemorrhagic center were CD68 positive, in brain slices taken at three days ( Figure 3 A) and even at 7, 14 and 28 days [ 21 ] after collagenase VII injection.…”
Section: Resultsmentioning
confidence: 99%